(untitled) (Journal of Nepal Geological Society, 2010)
The Late Pleistocene plant macrofossils from the Thimi Formation of the Kathmandu Valley have been reported in this paper. On the basis of 71 taxa from 39 families, seven plant macrofossil assemblages T-1 to T-7 were described from 18.5 m thick section of the Thimi Formation exposed at Madhyapur Thimi, Bhaktapur. Pinus, Abies, Tsuga, Carpinus, Sambucus, Rubus, Eurya, Potentilla and Scirpus are the common elements in the Thimi Formation. It is found that the cool temperate elements (Abies, Pinus, Tsuga, Picea, Taxus) were dominated over warm climatic elements (Quercus, Eurya, Pyracantha, etc.) during the deposition of the Thimi Formation. The underlying Gokarna Formation exhibited subtropical to warm temperate vegetation with the dominance of subtropical elements such as Eurya, Ficus, Zizyphus, etc. over temperate elements like Betula, Tsuga and Abies. During the depositional period of the Thimi Formation, this subtropical to warm temperate type of vegetation shifted to warm to cold temperate type with the abundant presence of gymnosperms and other evergreen taxa.